2006
DOI: 10.1242/dev.02589
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocyte marker-positive and -negative fetal liver cells differ significantly in their ability to regenerate the livers of adult rats exposed to retrorsine

Abstract: There was an error published in Development 133, 4269-4279.The Acknowledgements should have read 'Sponsored by grants CA42715, CA93840 and P20RR017695'. The authors apologise to readers for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
(43 reference statements)
1
22
0
Order By: Relevance
“…In situ labeling of cholangiocytes with MAb OC.10 promotes ductal morphogenesis Our laboratory has successfully used MAb OC.10 in combination with other antibodies to isolate antigenically defined subpopulations of OC.10-positive fetal cholangiocytes (Simper-Ronan et al 2006). In the course of the present investigations, we discovered that within an hour of injection of MAb OC.10 into the spleen of newborn Fisher rats, the antibody appeared exclusively on the surface of intraportal/intralobular bile ducts where it remained for at least 5 h post-injection (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ labeling of cholangiocytes with MAb OC.10 promotes ductal morphogenesis Our laboratory has successfully used MAb OC.10 in combination with other antibodies to isolate antigenically defined subpopulations of OC.10-positive fetal cholangiocytes (Simper-Ronan et al 2006). In the course of the present investigations, we discovered that within an hour of injection of MAb OC.10 into the spleen of newborn Fisher rats, the antibody appeared exclusively on the surface of intraportal/intralobular bile ducts where it remained for at least 5 h post-injection (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…One such antibody, MAb OC.10, has been shown to recognize an epitope shared by fetal liver ductal cells, oval cells, mature bile duct cells (cholangiocytes), and hepatocellular carcinomas with oval cell characteristics but not by hepatocytes (Hixson et al 2000). Because of its restricted surface expression profile, MAb OC.10 has been used in combination with other lineage-specific antibodies to isolate antigenically defined subpopulations present during liver development, renewal, and carcinogenesis (Simper-Ronan et al 2006). In the present study, we have shown that intrasplenic injection of MAb OC.10 into newborn rat pups strongly labels intrahepatic bile duct cells also positive for the bile duct marker OV-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High passage BDEC were sorted using the MACS MS column from Miltenyi Biotec (Auburn, CA) following the manufacturer's protocol for magnetic labeling of cells using goat anti-mouse IgG microbeads (Simper-Ronan et al, 2006). BDEC at passage 99 and 60-70% confluence were harvested with trypsin, washed with PBS and resuspended in complete BDEC medium.…”
Section: Methodsmentioning
confidence: 99%
“…These cells showed excellent repopulation capacity. Interestingly, if cell populations were depleted of CMP-FLEC, the repopulation potential was severely diminished (Simper-Ronan et al, 2006). Finally, studies have demonstrated that immuno-isolated delta-like-1-positive (Dlk-1 + ) rat fetal liver cells can account for the repopulation capacity of the FLEP (Oertel et al, 2008).…”
Section: Disease Models and Mechanisms 117mentioning
confidence: 99%